2016
DOI: 10.1038/srep20574
|View full text |Cite
|
Sign up to set email alerts
|

The miR-130 family promotes cell migration and invasion in bladder cancer through FAK and Akt phosphorylation by regulating PTEN

Abstract: Bladder cancer causes an estimated 150,000 deaths per year worldwide. Although 15% of the recurrent bladder cancer becomes an invasive type, currently used targeted therapy for malignant bladder cancer is still not efficient. We focused on the miR-130 family (miR-130b, miR-301a, and miR-301b) that was significantly upregulated in bladder cancer specimens than that of the normal urothelial specimens. We analyzed the functional significance of miR-130 family using a 5637 bladder cancer cell line and revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
93
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 69 publications
3
93
0
Order By: Relevance
“…For instance, miR-23b could function as a tumor suppressor that present downregulation in stomach cancer (35) and bladder cancer (36). Whereas the miR-130 family have been identified as upregulated in many cancer types that representing putative oncogene (37,38). This pan-cancer wide meta-profiling analysis indicated that the comprehensive investigation of the database may help to illuminate the complicated relationship between miRNAs and cancers and develop more effective treatment strategies for cancers.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, miR-23b could function as a tumor suppressor that present downregulation in stomach cancer (35) and bladder cancer (36). Whereas the miR-130 family have been identified as upregulated in many cancer types that representing putative oncogene (37,38). This pan-cancer wide meta-profiling analysis indicated that the comprehensive investigation of the database may help to illuminate the complicated relationship between miRNAs and cancers and develop more effective treatment strategies for cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Also, miR-301a is reported to promote colorectal cancer cell growth and invasion by directly targeting SOCS6 [37]. Meanwhile, Egawa and his colleagues showed that the miR-130 family promotes cell migration and invasion in bladder cancer through FAK and Akt phosphorylation by regulating PTEN [38]. The current study focused on the functions of miR-301a and its molecular mechanisms in MM.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, miR-130b was demonstrated to have tumor suppressive and cancer-promoting properties depending on the tumor type. miR-130b is highly expressed in melanoma (9), gastric (10), bladder (11) and colorectal cancer (12), esophageal squamous cell carcinoma (13) and glioma (14), but significantly and poorly expressed in papillary thyroid carcinomas (15), endometrial cancer (16), pituitary adenomas (17) and pancreatic cancer (18). Previously, miR-130b was observed to be overexpressed in glioma tissues, while the suppression of the expression of miR-130b via peroxisome proliferator-activated receptor-γ (PPAR-γ) inhibited the proliferation and invasive activity of glioma (14).…”
Section: Introductionmentioning
confidence: 99%